FEATURES OF CONSERVATION OF ABANDONED BUILDINGS AMONG THE TRIBES OF THE MAYKOP-NOVOSVOBODNENSKAYA COMMUNITY (ON THE MATERIALS OF NOVOTITAROVSKOYE-14 AND TUZLA-15 SETTLEMENTS) - Korenevskij, Sergej Nikolaevic (History, Archeology and Ethnography of the Caucasus, 2023)
The article aims to introduce the material on the new Maykop settlement Novotitarovskoye-14 and, to provide the description according to archaeological data of the conservation of the Maykop semi-dugout pits, as well as to discuss the construction of a portable hearth at the settlement Novotitarovskoye-14. The materials are compared with the finds at the Maykop settlement Tuzla-15. The methodology involves the description of the source, the analysis of finds and analogies, the definition of cultural affiliation and chronology. The article also provides the results of radiocarbon dating of materials from the Tuzla-15 settlement and osteological analysis of materials from Kurgan 12 of the Novotitarovskoye-14 group and the Tuzla-15 settlement. The Novotitarovskoye-14 settlement was discovered in 2014 by N.F. Shevchenko, the Tuzla-15 settlement was excavated by S.N. Korenevsky in 2012-2015 and described in a monograph. On both settlements, semi-dugout pits filled with pottery shards, animal bones and small tools in the form of pebbles, fragments of grain grinders were uncovered. At the settlement of Novotitarovskoye-14, the adobe furnace hearth, as well as a large fragment of the brazier were recorded. These findings prove that the Maykop population might have used portable hearths, which were lit outside their buildings. In both settlements, in the filling of abandoned buildings, a layer of ash from a fire that burned outside was recorded. The analysis of osteological findings clearly reflects that the majority of bones belong to large and small cattle. Single horse bones were found at Novotitarovskoye-14 settlement. The settlement of Novotitaroovskoye-14 belongs to the Maykop variant of the Maykop-Novosvobodnenskaya community, and the settlement of Tuzla-15 belongs to the similar Psekup variant of the Maykop-Novosvobodnenskaya community. The date of the first settlement cannot be determined precisely within the framework of the existence of the Maykop sites. The date of settlement of Tuzla-15 belongs to the final stage of the Maykop-Novosvobodnenskaya community.
Keywords: Maikop culture; ceramics; settlement; dwelling; kurgan; stratigraphy; osteology; tradition